Predictors of the existential dimension of gerotranscendence in women. Intergenerational differences - Kozerska, Agnieszka (Kwartalnik Naukowy Fides et Ratio, 2021)
Objectives: The purpose of this research is 1. to verify if older women (60+) differ from younger women in terms of the level of spiritual/cosmic transcendence. 2. To determine in which circumstances spiritual/cosmic transcendence grows in each of the research groups. Method: The research was carried out in Poland. Research subjects: 253 women aged between 20 to 89. Hierarchical regression analysis was used in the research taking into account two models. The research sample was divided to two groups: (1.) Younger group - aged between 20 to 49, and (2.) Older group - aged between 60 to 89. In the first stage, for each compared group separately, the model presenting the connection between cosmic gerotranscendence and the set of variables considered in the literature to be gerotranscendence correlates were analysed: Health condition and engagement in life, The feeling of sense in life, Wisdom, Recent experiencing a difficult life situation, The feeling of loneliness. Next, it was verified to what extent religious activity undertaken by women subject to the research related with creating a relationship with God improves parameters of model created in the first stage. Results: The level of spiritual/cosmic transcendence is higher in older women. In the group of both younger and older women the level of dependent variable increases in persons who actively look for the sense in life and are characterised by a high level of emphatic wisdom. A significant predictor in both compared groups is activity related to the search for God together with other people. In the group of younger women, an additional predictor is also experiencing difficult life situations within the past 6 months. Conclusion: The obtained models show that in the process of development towards spiritual transcendence relations with other people are essential for women who actively search for the sense in life. It refers in particular to relations with others in the context of religious engagement.